Ответы и объяснения

2014-01-10T08:57:24+00:00
2x^2+5x−12=0
a=2b=5c=12
D=b24ac=524·2·(−12)=25+96=121
x1=1,5
x2=−4

3x^25x−2=0
D=b24ac=(−5)24·3·(−2)=25+24=49
x1=2
x2=−0,333

6x^2 - 17x + 5 = 0
D = (-17)2 - 4·6·5 = 169
x1=1/3   x2=2.5

-5x2 + x + 6 = 0
D = 12 - 4·(-5)·6 = 121
x1=1.2  x2=-1

---------------------------------------------------

(x-5)^2-x+3=0
x^2-10x+25-x+3=0
x^2-11x+28=0
D = (-11)2 - 4·1·28 = 9
x1=4  x2=7


(7-x)(7+x)+3x^2=11x+34
49-x^2+3x^2=11x+34
2x^2-11x+15=0
D = (-11)2 - 4·2·15 = 1
x1=2.5 x2=3